Towards the Changes of the Concept of Autonomy in Bioethics - Drozenová, Wendy (Teorie vědy / Theory of Science, 2024)
The introduction is dedicated to the work of Ladislav Tondl, and his contribution to the Czech milieu. It tries to briefly summarize some of his methods and main ideas in the fields of technology assessment and theory and ethics of science that are giving us important impulses today; some of Tondl’s critical ideas of science are applied in the second part of the contribution. Technization of medicine resulted in breach of ethical rules in research on human subjects. Implementation of the principle of autonomy (Belmont Report) caused the shift from the paternalistic model of bioethics to the liberalistic one; since the 1990s, there has been post-liberalistic model. In the CR, due to the value lag the liberalistic model still tends to be established. The concept of autonomy is not unambiguous, it is open to various interpretations, but it is necessary and it is used even in contemporary care ethics. (Non-peer-reviewed essay on the occasion of Ladislav Tondl’s 90th birthday.)